A Clinical Case Report of Virechana Karma and Tuvaraka Rasayana in Ekakushta w.s.r Psoriasis - Rudranaikar, Basanaik D; Bagad, Subhas V (International Research Journal of Ayurveda & Yoga, 2022)
The skin is the boundary between human being and the world surrounding him. This is an important sense organ, the largest organ, and plays a major role in controlling the heat and water loss. Psoriasis is an autoimmune disease in which scaling and itching in the papulo squamous lesion of skin disturbs the daily routine of the patients. Because of its recurrent nature the disease has remained a great problem. There is no certain cure for this disease. Modern medicine provides symptomatic relief but also has side effects in long course. The ayurvedic diagnosis is considered as Ekakushta (Psoriasis) which is Vata Kapha predominant. This is best treated with panchakarma procedures, as the principle of treatment of all types of Kushta is Samshodhana (Purification) along with Samshamana (Pacification) drugs. Hence here an attempt made to analyse best treatment for psoriasis in ayurveda with well documented results. The present case shown significant result.